ANALISIS USAHA AGROINDUSTRI SUSU BUBUK KEDELAI (Studi kasus Industri Sumber Gizi Nabati (SGN) Di Kota Pekanbaru) - Sigit Santoso; Suardi Tarumun; Eliza Eliza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study is to : 1) Analyze revenue agroindustrial processing soybean milk powder SGN in Pekanbaru. 2) Analyzing profitalitas and efficiency of agroindustrial processing enterprises of soybean milk powder SGN in Pekanbaru. This research was carried out on an industrial soybean milk powder contained in Pekanbaru namely soybean milk powder industry SGN ( Source Nutrition Plant ) located at Jalan Ujung village Sidomulyo Seminai Eastern District of Marpoyan Peace RT 01 RW 08. Research was conducted on December 23, 2015 until January 25, 2016. The data used in this research is the primary data and secondary data. This study uses the case study method, which is a method of direct observation of the place of destination research. Based on data obtained will then be tabulated and analyzed according to the needs of research or as research purposes. The first objective of this research is to analyze the profit made by the agro-industry powdered soy milk. Based on data obtained will then be tabulated and analyzed according to the needs of research or as research purposes. The first objective of this research is to analyze the profit made by the agro-industry powdered soy milk. The purpose of this study were analyzed by calculating the net profits of the agro-industry and analyzes the value of depreciation of equipment. The second objective of this research is to analyze the efficiency of agroindustrial agroindustrial soy milk powder. The purpose of this study was analyzed using analytical models of Return Cost Ratio ( RCR ). From research conducted in the agro-industry effort soybean milk powder in Pekanbaru City SGN can be summarized as follows.           Total costs incurred by employers for Rp.44.551.450/month. Revenue obtained businessman Rp . 64 million per month. Gains derived businessman Rp 19,448,550 / month and the value of agro-industry profitability soybean milk powder amounted to 30.39 % . So agroindustrial businesses profitable soybean milk powder for the value of profitability > 0.2. Agroindustrial businesses soy milk powder has been efficient for the R / C ratio of more than one in the amount of 1.44 means that every Rp.1,00 costs incurred in agroindustrial enterprises provide soybean milk powder amounted to 1.44 times the acceptance of the costs incurred. Key word: Agroindustrial soy milk powder, Revenues and Profits.